2022
DOI: 10.1039/d2ra02137d
|View full text |Cite
|
Sign up to set email alerts
|

Thermostable bacterial laccase for sustainable dyeing using plant phenols

Abstract: Laccase is regarded as an efficacious eco-friendly enzyme in various industries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…The purification of LacT resulted in an ∼38% yield and an ∼3.2 purification fold. The homogeneity of purified LacT (molecular weight of ∼65 kDa) was confirmed by SDS-PAGE and zymogram analysis . In this study, we performed peptide mass fingerprinting by the MALDI-TOF/MS-MS technique to further identify and characterize LacT in detail.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The purification of LacT resulted in an ∼38% yield and an ∼3.2 purification fold. The homogeneity of purified LacT (molecular weight of ∼65 kDa) was confirmed by SDS-PAGE and zymogram analysis . In this study, we performed peptide mass fingerprinting by the MALDI-TOF/MS-MS technique to further identify and characterize LacT in detail.…”
Section: Resultsmentioning
confidence: 99%
“…LacT was purified by a series of chromatographic techniques, namely, anion exchange and size exclusion chromatography. The purity was confirmed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and zymogram analysis. , This study focuses further on the biophysical characterization of LacT and its potential application in bioremediation.…”
Section: Experimental Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Laccases (EC 1.10.3.2) are oxidoreductases that can catalyze the oxidation of several compounds, by producing water from molecular oxygen [ 1 ]. Many different laccases are produced from various organisms such as bacteria and fungi [ 2 , 3 , 4 , 5 ]. One of the most used laccases is the laccase derived from the mushroom Trametes versicolor ( T. versicolor ).…”
Section: Introductionmentioning
confidence: 99%
“…Polyphenols, pyrogallol, and gallic acid can be extracted from tea leaves, gallnuts, and other plants [ 27 , 28 , 29 ]. Modern hair dyes use pyrogallol and gallic acid, revolutionary coating methods with different chemical structure mechanisms that are safe compared with the existing standard dyes [ 30 , 31 ]. Mohamed El-Wekil et al [ 32 ] reported that the hydroxyl groups in pyrogallol complexed with Cu(II)Cl 2 and formed a coordination complex between Cu and a catechol moiety.…”
Section: Introductionmentioning
confidence: 99%